Pengaruh Motivasi Terhadap Kinerja Pegawai Sekolah Menengah Pertama Yogyakarta - Herry Purwanto (SMARTINDO, 2023)
This study aims to determine the effect of rewarding on employee performance at SMP Islam Terpadu Abu Bakar Yogyakarta. The method used is explanatory research with a sample of 55 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study, the variable giving rewards obtained an average score of 3.402 with good criteria. Employee performance variables obtained an average score of 3.838 with good criteria. Reward giving has a positive and significant effect on employee performance with the regression equation Y = 9.047 + 0.862X, and the correlation coefficient value of 0.774 or having a strong level of relationship with a determination value of 59.9%. Hypothesis testing obtained a significance of 0.000 <0.05.